Implementation of Diversion for Children Facing the Law at the Palembang Class I Correctional Center - Aprizayanti Anggelina; Alfitri Alfitri; Muhammad Husni Thamrin; Andries Lionardo (Eduvest - Journal of Universal Studies, 2026)
This study examines the application of diversion in the juvenile criminal justice system with a focus on the role of community research (litmas) and the recommendations of Community Supervisors (PK) in Bapas Class I Palembang. This study highlights the practice of diversion in handling children's cases, the position of litmas and PK recommendations in decision-making, as well as institutional barriers that affect its effectiveness. The research uses a socio-legal qualitative approach with a case study design, through interviews with PK, law enforcement officials, and related stakeholders, as well as a review of litmas documents, diversion agreements, case decisions, and regulations. The analysis was carried out thematically by triangulating sources. The results of the study show that the success of diversion is highly dependent on the quality of social assessment in litmas, the ability to facilitate deliberation, and the sustainability of post-agreement supervision. Litmas acts as a tool for mapping children's needs and risks, the basis for guidance recommendations, and a means of accountability. The main obstacles include weak coordination across institutions, differences in interpretation of procedures, limited resources, and non-optimal monitoring mechanisms. This study recommends strengthening the standardization of litmas, increasing the capacity of diversion facilitators, integrating support services, and developing a measurable monitoring system so that diversion is truly oriented towards the recovery of children and victims.